The future of small farms in Asia - Otsuka, Keijiro; Liu, Yanyan; Yamauchi, Futoshi (Wiley, 2016)
Farms throughout Asia are predominantly small. By nature, small farms use labour‐intensive production methods. The question arises as to the viability of small farms in the face of the rapidly increasing wage rate in most Asian countries. There is also indication that the production efficiency of small farms has declined relative to large farms in many Asian economies, indicating the increasing disadvantage of small farms in Asia. Therefore, this study argues that unless new policy measures are taken to expand farm size, Asia as a whole is likely to lose comparative advantage in agriculture and become an importer of food grains in the future.